PENGARUH AKTIVITAS GALERI INVESTASI SYARIAH, MODAL MINIMAL, DAN EFIKASI KEUANGAN TERHADAP MINAT INVESTASI - Mohammad Adi Pramana Putra; Syafrudin Arif Marah Manunggal (LPPM Institut Pendidikan Nusantara Global, 2023)
The problem in this research is the lack of investment interest in students through education and training. This is because it is not supported by minimum capital and financial efficiency owned by students. Therefore this study aims to determine the effect of Islamic investment gallery activities, minimum capital, and financial efficacy on investment interest. Either partially or simultaneously. The results showed that: (1) there was a positive and significant influence between Islamic investment galleries on investment interest, as seen from the T-value of 2.859 > from T-table = 1.971 at a significance of 2.5%. (2) there is a positive and significant influence between minimum capital on investment interest, as seen from the T count of 3,066 > from T table = 1.971 at a significance of 2.5%. (3) there is a positive and significant influence between Financial Efficacy on investment interest, as seen from the T count of 6.363 > from T table = 1.971 at a significance of 2.5%. The practical implications of this research are: (1) if students start to feel the benefits of the education provided by Islamic investment galleries, the interest in investing will be even higher. (2) if the minimum capital can be reached by students, it will have an impact on increasing interest in investment. (3) if students have high financial efficacy it will have an impact on increasing investment interest.